2011
DOI: 10.1002/bit.23182
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular peptide delivery using amphiphilic lipid‐based formulations

Abstract: Peptides, highly diverse by their nature, are important biochemical and pharmaceutical tools: ligands for cellular receptors, transcription factors, immunosuppressants, vaccines, etc. As the majority of their targets are intracellular, peptides need to cross the plasma membrane and gain access to the cytoplasm. However, due to their physicochemical properties, most peptides need to be entrapped by a molecular vehicle to be able to reach the cytosol compartment. In this study, we present new biological tools to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Enzymes are especially vulnerable, since minor alterations in protein structure can lead to loss of activity. PULSin was selected as a delivery vehicle, since this lipid formulation has previously been shown to form a complex with proteins without affecting protein activity [37]. Moreover, while most protein delivery strategies require complex conjugation procedures, a protein-PULSin complex can be formed with a simple mixing step.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Enzymes are especially vulnerable, since minor alterations in protein structure can lead to loss of activity. PULSin was selected as a delivery vehicle, since this lipid formulation has previously been shown to form a complex with proteins without affecting protein activity [37]. Moreover, while most protein delivery strategies require complex conjugation procedures, a protein-PULSin complex can be formed with a simple mixing step.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, while most protein delivery strategies require complex conjugation procedures, a protein-PULSin complex can be formed with a simple mixing step. Additionally, PULSin has been shown to permit cellular internalization and endosomal escape of proteins [37]. In this study, pyruvate decarboxylase was complexed with PULSin in order to enable intracellular delivery.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1920 People found that the introduction of peptide groups into lipids can prolong their half-life in vivo and enhance targeting thereof. 21 …”
Section: Introductionmentioning
confidence: 99%